Nursing Records of Orthopedic Patients Treated with Non- Steroidal Anti-inflammatory Drugs; NSAIDs, Songklanagarind Hospital: A Retrospective study - Hasap, Manee; Hasap, Mongkolchai; Chauy-upakan, Prapai; Thiangchanya, Pratyanan (Princess of Naradhiwas University Journal, 2022)
This research aimed to study the nursing’s record on care of orthopedic patients treated with NSAIDs. The theoretical framework of the study was derived from the concept of nursing process. The 276 subjects were orthopedic patients treated with NSAIDs admitted to the orthopedic ward of Songklanagarind Hospital between 1 January - 30 June 2017. The data were collected from medical record. The instruments composed of 2 parts: 1) patients’ general information including personal data, illness status and treatment, signs and symptoms during hospitalization, information about NSAIDs treated, and date of discharge, 2) the checklist for nursing record of orthopedic patients treated with NSAIDs including initial assessment form, medication record form, nursing problem list, nursing progress note, continuing nursing care plan and discharge summary, and graphic sheet record. Data were analyzed using descriptive statistics, which were frequency, percentage, mean, and standard deviation The study showed that the documents widely used in the hospital were 1) initial nursing assessment form including drinking, smoking and other narcotic substances history shown at 98.2%, 2) medication records which explicit electronic medication card at 96%, 3) explicit continuing nursing care plan and discharge summary form included how to use, side effects and how to behave for prevention of NSAIDs adverse reactions including help sources at 45.2% followed by 4) graphic sheet that recorded intake-output at 43.8%, 5) nursing problem list which records were corresponded with care objectives at 0.4% and 6) nursing progress note which none of problems and intervention on NSAIDs were mentioned at all.